(untitled) (Swiss Medical Weekly, 2018)
Of the two million people estimated to be newly infected with human immunodeficiency virus (HIV) every year, 95% live in poorer regions of the world where effective HIV treatment is not universally available. Strategies to reduce the spread of HIV infection, which predominantly occurs via sexual contact, are urgently required. In the absence of an effective vaccine, a number of approaches to prevent HIV infection have been developed. These include using potent anti-HIV drugs prophylactically, either through systemic administration or topical application to the mucosal tissues that HIV initially encounters during sexual transmission. Genetic deficiency of the chemokine receptor CCR5 provides individuals with a remarkable degree of protection from HIV acquisition. This is because CCR5 is the major coreceptor used by HIV to infect new target cells. Since CCR5 deficiency does not appear to carry any health disadvantages, targeting the receptor is a promising strategy for both therapy and prevention of HIV. In this review we first describe the advantages and limitations of the currently available strategies for HIV prevention, then we focus on strategies targeting CCR5, covering the progress that has been made in developing different classes of CCR5 inhibitors for prophylaxis, and the perspectives for their future development as new weapons in the global fight against HIV/AIDS.